Development of an Electronic Tracer System to Improve Medical Record Management and Healthcare Service Efficienc - Fadly, Fery; Sari, Fajar Yunita; Kurniasih, Dewi Lena Suryani; Febiani, Ani Nur (Jurnal Rekam Medis dan Informasi Kesehatan, 2024)
Tracer is a tool used to indicate when medical record files are borrowed or removed from the filing room. Field data indicates that the use of manual tracers has slowed down service, as staff often feel rushed when recording information on these tracers. As a result, manual tracers have been discontinued, leading to difficulties in tracking the whereabouts of files, delays in retrieving medical records, and a negative impact on patient care and the quality of hospital services. This study aims to design an electronic tracer system. The research is qualitative with a phenomenological design and employs the Rapid Application Development (RAD) method for system design. Data collection methods include interviews and observations. The study begins with identifying issues related to the use of manual tracers, analyzing system requirements, and designing the system, which includes creating context diagrams, Data Flow Diagrams (DFD), Requirement Tables (TRD), and activity diagrams for the electronic medical record tracer.